KETIKA KEBOLEHAN MENJADI TANGGUNG JAWAB: MENIMBANG KEMBALI POLIGAMI MELALUI PRINSIP KEADILAN DALAM HUKUM KELUARGA ISLAM - Muhammad Afif; Muh. Shahibul Rasyad (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
Polygamy is a critical issue in Islamic family law that continues to generate debate, particularly within contemporary multicultural societies. This article aims to analyze prophetic traditions (?ad?ths) on polygamy by emphasizing the concept of justice and its relevance to modern values of equality and humanity. This study employs a qualitative method using normative and contextual approaches through the analysis of ?ad?ths, classical Islamic jurisprudence, and contemporary scholarly perspectives. The findings indicate that polygamy in Islam is conditionally permitted, with justice as its fundamental requirement, particularly in fulfilling the material rights of wives. The Prophet’s traditions affirm limitations on the number of wives and position justice as the core principle rather than as a justification for unrestricted polygamy. In multicultural contexts, a contextual interpretation of ?ad?ths is essential to prevent injustice, especially toward women and children. This article concludes that polygamy is not an ideal practice encouraged in Islam but a conditional solution that must align with the objectives of Islamic law (maq??id al-shar?‘ah) and the principles of justice in modern social life.